Agriculture in African rural communities - Dupriez, Hugues; De Leener, Philippe; O'Meara, Bridaine (London : Macmillan Publishers in association with Terres et Vie and CTA, 1988)
This book aims at practitioners and students of agriculture and rural development and associated vocational and technical skills.
Translated from the French title "Agriculture tropicale en milieu paysan Africain"
Includes index.
Includes bibliographical references: p. 289-290.
hza 29/01/2019
Loans
Keywords: Tropical crops; Tropics; Agriculture; Crops and soils; Crops; Crops--Physiology.; Africa